2017
DOI: 10.1212/wnl.0000000000004057
|View full text |Cite
|
Sign up to set email alerts
|

Intake of dairy foods and risk of Parkinson disease

Abstract: Frequent consumption of dairy products appears to be associated with a modest increased risk of PD in women and men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
66
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 21 publications
5
66
0
2
Order By: Relevance
“…A meta-analysis of all prospective studies confirmed a moderately elevated risk of PD among persons with higher dairy product consumption. The combined RRs between extreme intake categories were 1.6 (95% CI: 1.3–2.0, p<0.0001) for men and women combined (176), findings that were recently substantiated (177). Although the higher concentration of pesticides and other toxins in milk and other dairy products has been pointed out as a potential explanation for the dairy link to PD, the inverse link between urate levels and dairy consumption has emerged as a similarly compelling hypothesis.…”
Section: Dietary Determinants Of Pdmentioning
confidence: 83%
“…A meta-analysis of all prospective studies confirmed a moderately elevated risk of PD among persons with higher dairy product consumption. The combined RRs between extreme intake categories were 1.6 (95% CI: 1.3–2.0, p<0.0001) for men and women combined (176), findings that were recently substantiated (177). Although the higher concentration of pesticides and other toxins in milk and other dairy products has been pointed out as a potential explanation for the dairy link to PD, the inverse link between urate levels and dairy consumption has emerged as a similarly compelling hypothesis.…”
Section: Dietary Determinants Of Pdmentioning
confidence: 83%
“…Several epidemiological studies have assessed the relationship between environmental factors and the risk of developing PD [18,65]. Some factors are likely to increase the risk, such as exposure to pesticides [66], traumatic brain injury [67], history of melanoma [68], consumption of dairy products [69] and high iron intake [70]. Reduced risks are associated with physical activity [71], mild smoking [72], tea [73], vitamin E [74], caffeine consumption [73], higher serum urate concentrations [75] and the use of ibuprofen and other common medications [76].…”
Section: Evidence From Epidemiological Studiesmentioning
confidence: 99%
“…Dairy consumption has been associated with an increased risk of PD in a number of studies and a recent meta‐analysis, possibly as a result of a greater intake of fat‐soluble toxicants. The evidence for association with dietary metal intake has been rather inconclusive so far, although a recent meta‐analysis suggested that high iron intake may be associated with increased risk in men and Western populations …”
Section: The Past 10 Yearsmentioning
confidence: 99%